2012
DOI: 10.1007/s13300-012-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Addition of Sitagliptin and Miglitol on Insulin-Treated Type 2 Diabetes

Abstract: IntroductionTo examine the efficacy of sitagliptin and miglitol when added to ongoing insulin treatment in a patient with type 2 diabetes who had undergone partial gastrectomy.MethodsContinuous glucose monitoring (CGM) was performed and either sitagliptin or miglitol, or both, were added to fixed-dose insulin therapy. Blood was drawn at 0, 30, 60, and 120 min after breakfast, and C-peptide, glucagon, glucagon-like peptide (GLP)-1, and glucose-dependent insulinotropic peptide (GIP) were measured.ResultsCGM show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A possible mechanism may be increased exposure of nutrients to the distal small intestine, where L-cells are located [ 32 , 34 36 ]. To confirm these results, we previously studied postprandial active GLP-1 levels in patients with type 2 diabetes treated with or without insulin and found that miglitol administration increased active GLP-1 levels in some, but not all, patients [ 10 , 11 ]. The effect of miglitol administration in the present study resulted in varying total or active GLP-1 levels in each patient, but no typical pattern was observed.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A possible mechanism may be increased exposure of nutrients to the distal small intestine, where L-cells are located [ 32 , 34 36 ]. To confirm these results, we previously studied postprandial active GLP-1 levels in patients with type 2 diabetes treated with or without insulin and found that miglitol administration increased active GLP-1 levels in some, but not all, patients [ 10 , 11 ]. The effect of miglitol administration in the present study resulted in varying total or active GLP-1 levels in each patient, but no typical pattern was observed.…”
Section: Discussionmentioning
confidence: 92%
“…Alpha-glucosidase inhibitors (a-GIs), another type of oral antidiabetic drug, also attenuate postprandial blood glucose fluctuations by delaying the absorption of digested carbohydrates from the small intestine [ 7 9 ]. Considering the different mechanisms of DPP-4 inhibitors and α-GIs, their use in combination therapy is promising for improving glycemic control [ 10 , 11 ]. The present case study aimed at examining the efficacy, through the use of a continuous glucose monitoring system (CGMS) [ 12 14 ] and hormone measurements, of a DPP-4 inhibitor (anagliptin) [ 15 ], and an α-GI (miglitol) when added to ongoing insulin treatment in patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…These patients demonstrated a low rate of hypoglycemia and a slight weight reduction 43,55. We previously reported that the combination of sitagliptin and insulin therapy presented beneficial effects in stabilizing glycemic control by stimulating endogenous insulin secretion and suppressing glucagon secretion 60. Vilsbøll et al previously reported in a 24-week study that the addition of sitagliptin to ongoing insulin therapy resulted in significant improvements in glycemic control, in comparison with the placebo treatment, by improving β-cell responsiveness 61.…”
Section: Gliptin Treatments In Combination With Insulinmentioning
confidence: 98%
“…We are also attempting to construct new regimens composed of basal insulin and multiple hypoglycemic agents, including DPP-4 inhibitors or GLP-1 analogs [32]. …”
Section: Discussionmentioning
confidence: 99%
“…To improve postprandial hypoglycemia, dipeptidyl peptidase-4 (DPP-4) inhibitors and GLP-1 analogs are other choices for use in combination with basal insulin [ 30 , 31 ]. We are also attempting to construct new regimens composed of basal insulin and multiple hypoglycemic agents, including DPP-4 inhibitors or GLP-1 analogs [ 32 ].…”
Section: Discussionmentioning
confidence: 99%